The dilemma of Hi-Tech babies [videorecording]. (Reproduced by Daughters of St. Paul, 1987)
Advances in technology have made procreation possible outside the marriage act by means of artificial insemination, surrogate motherhood and "in-vitro" fertilization. Shows Cardinal Lane, Fr. Albacete, Leslie Collins and popular news magazine host, Mary Richardson, in an open discussions of these complex and controversial issues.